2016
DOI: 10.1002/jcb.25796
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hedgehog Signaling in Chicken Embryonic Stem Cells Differentiation Into Male Germ Cells (Gallus)

Abstract: The study aims to analyze the key signaling pathways in regulating the process of embryonic stem cells (ESCs) differentiation into spermatogonial stem cells (SSCs). Based on RNA Sequencing result, we further explored the specific regulating mechanisms of Hedgehog (HH) signaling in this process. HH signaling was found to be a crucial signaling pathway participating in the differentiation process of ESCs to SSCs. In Retinoic acid (RA) induced in vitro differentiation assay, the expression of two germ cell marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Moreover, Wnt signaling pathway, a downstream signaling pathway of the Hedgehog signaling pathway plays a role in signal transduction in concert with other signal transduction pathways . It has been previously reported that Hedgehog signaling positively regulates the differentiation of chicken male germ cells . Thus, there is a crosstalk between Wnt signaling and Hedgehog signaling during the differentiation of male germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wnt signaling pathway, a downstream signaling pathway of the Hedgehog signaling pathway plays a role in signal transduction in concert with other signal transduction pathways . It has been previously reported that Hedgehog signaling positively regulates the differentiation of chicken male germ cells . Thus, there is a crosstalk between Wnt signaling and Hedgehog signaling during the differentiation of male germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that C2EIP interacts with PTCH2 at the intracellular membrane and thus speculated that C2EIP may regulate PGC differentiation by influencing HH signaling pathway activation. Therefore, we constructed lentiviral shRNA-IHH 15 and shRNA-PTCH2 vectors to investigate the function of HH signaling in the process of PGC generation (Supplementary Figure 6a-c ). ESC were transfected with shRNA-IHH or shRNA-PTCH2 in parallel with in vitro RA induction experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is supported by earlier studies showing that CRISPR/Cas9-mediated knockout of C2EIP in chick embryos significantly limited their development 13 and reduced PGC generation efficiency, and C2EIP overexpression promoted PGC generation. The GST pull-down assay showed that C2EIP interacted with PTCH2, an important membrane protein of the Hedgehog (HH) signaling pathway, which can upregulate germ cell differentiation and PGC generation 15 . However, whether C2EIP function is associated with HH signal activation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the potential mechanism of the regulation of FGSC proliferation or stemness is beneficial to understanding how normal egg and ovary function is maintained. As a canonical signaling pathway, the hedgehog (Hh) pathway plays a key role in the regulation of stem cell proliferation and embryonic development, as well as cellular communication [8][9][10]. Studies showed that mice were subjected to serious damage in folliculogenesis when a mutation was introduced in the Hh pathway [11].…”
Section: Introductionmentioning
confidence: 99%